Islamic Art And Eschatology In The Kemas Community Dakwah At Media: An Quran Rhetorical Approach - Mohd Nathir, Khairul Asyraf; Samah, Rosni; Nawi, Amani; Abdul Majid, Mohamad Yazid; Abd Zaman, Bushro (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines the concept of eschatology in Arabic literature, focusing on the